PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI ANDROID MENGGUNAKAN SOFTWARE SMART APPS CREATOR 3 (SAC) MATERI SISTEM TATA SURYA KELAS VI SEKOLAH DASAR - wewin widiansyhrani (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
The objectives of this study include: 1) describing aspects used to develop the learning media of the solar system sustem, 2) describing the design of solar system learning media, 3) describing the feasibility test of solar system learning media, and 4) describing the results of reflection of solar system learning media. This research provides insight and knowledge about the process of creating android-based learning media using Smart Apps Creator software, teachers get ease in delivering materials through this media and provide learning motivation to students. Research and development (R&D) methods. Research and Development is a research method to produce products and test the effectiveness of products produced (Sugioyono, 2016:407). According to Nana Syaodih Sukmadinata (2009: 164), Research and Development (R&D) is a process or steps to develop a new product or improve an existing product, which can be accounted for. research and development measures used are based on addie model, namely Analysis, Design, Development, Implementation, and Evaluation.